Religious Moderation in Madrasah: Religious Character Strengthening and Tolerance - Zaenal; Sulaiman, Nasrullah; Lubis, Ervy Alinda (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This study aims to examine religious moderation in madrasah, focusing on strengthening character and religious tolerance. The study uses a descriptive qualitative research method, with the subjects being students and teachers at one of the madrasas in Indonesia. Data were collected through interviews and observations, then analyzed using descriptive analysis techniques. The results show that madrasas play an important role in teaching religious values and strengthening students' character, as well as developing religious tolerance to foster harmony and diversity in society. Strengthening character in madrasah can be achieved through religious teaching and the development of students' personalities by providing positive examples in daily life. Religious tolerance can be strengthened by teaching Islamic principles that promote tolerance, engaging in social activities together, and interfaith dialogue. However, there are several challenges in strengthening religious moderation in madrasah, such as the lack of available facilities and supporting curricula, as well as discrimination and intolerance in society. Therefore, support from the government and all relevant stakeholders is needed to strengthen educational programs that emphasize values of tolerance and harmony. Overall, this study shows that madrasas can play a role as Islamic educational institutions that can strengthen students' character and develop religious tolerance, thereby helping to build harmony and diversity in society.